Internship program and career preference : a case study of Politeknik Ibrahim Sultan final year students / Mohamad Azhar Othman and Rossi Gundie Anak Julius - Othman, Mohamad Azhar; Julius, Rossi Gundie (Faculty of Hotel and Tourism Management, 2013)
The employments of the graduated students were identified every year and the result shows that 29.9% students who graduated in 2012 joined the hospitality industry. The polytechnics were aware of this scenario due to the figure are not met the objective of polytechnic itself to ensure they can produce the students to enter related industry. Therefore, this paper attempted to discover the importance of positive and negative experience, internship satisfaction and career preference. A total of 251 cases were gathered from Diploma in Hotel and Catering Management final year students in Politeknik Ibrahim Sultan. Research finding reveal that the important of internship experience, internship satisfaction and career preference. The implication and limitation of this study are presented and discussed.